ASSESSMENT OF DIETARY PATTERN IN ASSOCIATION WITH NON-COMMUNICABLE DISEASE RISK FACTORS AMONG MIDDLE ADOLESCENTS IN RAWALPINDI - Zahid, Maryam; Khalil, Hafsa; Iqbal, Usman; Mumtaz, Sehrish; Hassan, Mawara; Khan, Shanzah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the dietary pattern in association with non-communicable disease risk factors among middle age adolescents in Rawalpindi. Study Design: Descriptive cross-sectional study. Place and Duration of Study: City School (Rawal Campus), Rawalpindi and Allied School (Ghauri town campus), Rawalpindi, from Jun to Jul 2021. Methodology: The self-administered questionnaire used in this study included numerous questions related to the sociodemographic background of students and a short food frequency questionnaire (FFQ) to assess the usual dietary intake of adolescents. Students were selected through Simple Random sampling. Data was entered and analyzed using SPSS-23. Results: A total of 145 students mean age 16.2 ± 1.92 years participated in this this study out of which 97 (66.9%) were male and 48 (33.1%) were female. Out of 66 (45.5%) students were from Allied School and 79 (54.4%) students were from City School, Rawalpindi participated this study. In this 60% of the participants were had normal body mass index (18.5-24.9), 4 (2.8%) students consume alcohol and 2 (1.4%) were smoker. Most of the participants were active 88 (62%). The dietary patterns of young adolescents determines that choices of most of the food items were not according to the standard guidelines Conclusion: This research have highlighted the visible shift in dietary intake among adolescent of Rawalpindi. This shift will have major implications for the double burden of malnutrition that currently exists and will contribute to the rising prevalence of NCDs.